MENINGKATKAN HASIL BELAJAR PAI MATERI QURBAN DAN AQIQAH MELALUI PEMBELAJARAN KOOPERATIF MODEL TGT - yusnidar abdullah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
In particular, this study aims to determine whether learning Islamic Education using Cooperative Learning TGT models can improve student learning outcomes and improve mastery of Islamic Religion subject matter in class IX of SMP Negeri 1 Darul Aman, Darul Aman District. Classroom Action Research (CAR) is carried out using two rounds of action research. Each round consists of four stages, namely: design, activity, observation and reflection. The target of this study is the class IX students of 1 Darul Aman Middle School, amounting to 40 people. Consisting of 33 male students and 7 female students. Data obtained in the form of test results and observation sheets of teaching and learning activities. From the results of the analysis it was found that student learning achievement experienced an increase from cycle I to cycle II, namely, cycle I 70.63 and cycle II 83.88. So from the results of these studies it can be concluded that through the use of cooperative learning the TGT model has a positive impact and has an advantage in improving the learning outcomes of Islamic Education Class IX Students at SMP Negeri 1 Darul Aman, Darul Aman District.